Integrating climate‐change refugia into 30 by 30 conservation planning in North America. Issue 2 (11th January 2023) - Saunders, Sarah P; Grand, Joanna; Bateman, Brooke L; Meek, Mariah; Wilsey, Chad B; Forstenhaeusler, Nicole; Graham, Erin; Warren, Rachel; Price, Jeff
Abstract : Countries have set targets for conserving natural areas to mitigate biodiversity loss, such as the protection of 30% of lands by 2030, commonly referred to as "30 by 30". Yet strategic conservation planning to align those targets with climate‐change refugia is lacking. We investigated the feasibility of achieving 30 by 30 in North America by assessing the proportions of state/provincial/territorial land projected to provide refugia for terrestrial biodiversity and the proportions of those refugia that are currently protected. We also conducted a reserve selection prioritization to identify priority areas that complement the current protected area network and capture refugia for seven taxonomic groups. In North America, <15% of refugia are protected, but ample opportunity exists to expand protection if warming is limited to 2°C. Beyond 2°C, however, the majority of refugia will occur only at high latitudes and elevations. Incorporation of refugia into 30 by 30 efforts will facilitate species persistence under climate change.